2018
DOI: 10.1136/medethics-2017-104722
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ understanding of the legislation governing research involving adults lacking mental capacity in England and Wales: a national survey

Abstract: ObjectiveTo examine health and social care professionals’ understanding of the legislation governing research involving adults lacking mental capacity in England and Wales.MethodsA cross-sectional online survey was conducted using a series of vignettes. Participants were asked to select the legally authorised decision-maker in each scenario and provide supporting reasons. Responses were compared with existing legal frameworks and analysed according to their level of concordance.ResultsOne hundred and twenty-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…New interventions require robust evaluation to examine benefit and potential of harm for the population intending to benefit [5,6]. Studies, especially clinical trials in palliative care, are often compromised by insufficient sample size to detect change [7][8][9][10][11][12][13], and impaired understanding of legislation governing research involving adults with impaired capacity [14]. The ethical challenges of recruiting individuals with impaired capacity are examined across fields involving adults with serious illness including palliative care [15], dementia [16][17][18], mental health [19], and intensive care [20].…”
Section: Introductionmentioning
confidence: 99%
“…New interventions require robust evaluation to examine benefit and potential of harm for the population intending to benefit [5,6]. Studies, especially clinical trials in palliative care, are often compromised by insufficient sample size to detect change [7][8][9][10][11][12][13], and impaired understanding of legislation governing research involving adults with impaired capacity [14]. The ethical challenges of recruiting individuals with impaired capacity are examined across fields involving adults with serious illness including palliative care [15], dementia [16][17][18], mental health [19], and intensive care [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring the protection of the groups considered most vulnerable to potential harm is an important aim of research ethics, and also those with professional responsibility to care for groups unable to protect their interests through informed consent. However, our survey of health and social care professionals, which explored their knowledge about the legislation governing research involving adults lacking capacity, revealed a deeper and more worrying issue about their attitudes towards the inclusion of people with impaired decision-making capacity in medical research [29]. A number of participants stated that people who lack capacity should never be included in research, both from an ethical and a legal perspective, and some voiced concerns that only the person's medical practitioner or an appointed judge should have the authority to decide about research participation, and only when it is determined to be in their best interests to take part [29].…”
Section: Paternalistic Attitudes To Protection From Researchmentioning
confidence: 98%
“…However, our survey of health and social care professionals, which explored their knowledge about the legislation governing research involving adults lacking capacity, revealed a deeper and more worrying issue about their attitudes towards the inclusion of people with impaired decision-making capacity in medical research [29]. A number of participants stated that people who lack capacity should never be included in research, both from an ethical and a legal perspective, and some voiced concerns that only the person's medical practitioner or an appointed judge should have the authority to decide about research participation, and only when it is determined to be in their best interests to take part [29]. There was a widespread lack of understanding that the decision about research participation should not be based on a determination of best interests [52] and should instead be based on what the person's wishes and feelings about taking part would be, which can only be determined through consulting with those that know them well.…”
Section: Paternalistic Attitudes To Protection From Researchmentioning
confidence: 98%
See 2 more Smart Citations